2010
DOI: 10.1111/j.1468-1331.2009.02781.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb involvement in adult‐onset primary dystonia: frequency and clinical features

Abstract: The lower limb is an uncommon but possible topographical site of dystonia in adulthood that should be kept in consideration during clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Second, since we collected data for age at onset retrospectively, some information may have been inaccurate. We consider this unlikely given that we have previously shown that patients achieve high test–retest reliability in reporting age at dystonia onset 16. Although some tremor events documented herein manifested themselves before patient referral to the recruiting centre, some patients were followed-up for several years, and tremor events were recorded during the clinical follow-up.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Second, since we collected data for age at onset retrospectively, some information may have been inaccurate. We consider this unlikely given that we have previously shown that patients achieve high test–retest reliability in reporting age at dystonia onset 16. Although some tremor events documented herein manifested themselves before patient referral to the recruiting centre, some patients were followed-up for several years, and tremor events were recorded during the clinical follow-up.…”
Section: Discussionmentioning
confidence: 85%
“…First, it is not a population-based study. Nevertheless, recruiting consecutive patients in a multicentre setting yielded a large case series that resembles the demographic and clinical features of the Italian PAOD population 16. Second, since we collected data for age at onset retrospectively, some information may have been inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most common treatment for any type of lower extremity dystonia includes Botox and trihexyphenidyl. 21 Only 2 cases were found describing nonmedicinal or noninvasive management of task-specific lower extremity dystonia. 3,36 In 1 case, functional electrical stimulation was shown to improve but not fully resolve the patient's gait dysfunction.…”
Section: Treatment Of Runner's Dystoniamentioning
confidence: 99%
“…9,11,16,26,31 Whereas primary focal dystonia is relatively rare, task-specific lower extremity dystonia is even less prevalent. Within a specialized movement-disorder clinic, only 4 (0.7%) of 579 individuals with primary focal dystonia had lower extremity dystonia, 21 and none of these individuals presented with the specific movement pattern described in this case. With growing numbers of runners, including participants in high-mileage events (marathons and ultra-marathons), a higher prevalence of lower extremity dystonia, including runner's dystonia, is likely.…”
mentioning
confidence: 99%
“…It should therefore prompt the physician to evaluate secondary causes of dystonia. Moderate to marked improvement with BoNT is also observed in patients with rare primary lower limb dystonia [Duarte et al 1995;Schneider et al 2006a;Singer and Papapetropoulos, 2006;Martino et al 2010;Pont-Sunyer et al 2010].In summary, treatment with BoNT-A is an effective treatment in many of the focal dystonias, with good evidence in CD and BSP, and is therefore the first-line intervention for most of the focal dystonias. Although BoNT-B has only been thoroughly evaluated in CD, a comparable effect may be expected for the other focal dystonia subtypes but this remains largely unproven.…”
mentioning
confidence: 96%